1985
DOI: 10.1042/bj2270573
|View full text |Cite
|
Sign up to set email alerts
|

Co-purification of galactosyltransferases from chick-embryo liver

Abstract: Two galactosyltransferases with nearly identical Mr values were purified 5000-7000-fold from microsomal membranes of chick-embryo livers by using several affinity columns. One enzyme transfers galactose from UDP-galactose to form a beta-(1----4)-linkage to GlcNAc (N-acetylglucosamine) or AsAgAGP [asialo-agalacto-(alpha 1-acid glycoprotein)]. The other enzyme forms a beta-(1----3)-linkage to AsOSM [asialo-(ovine submaxillary mucin)]. Both enzymes were solubilized (85%) from a microsomal pellet by using 1% Trito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…It was reported that the lactose synthetase and other p1-4GalTs are activated by Mn2+, which is involved in maintaining the structural integrity of the enzyme, and the optimal Mn2+ concentrations of these enzymes were in the range of 10-15 mM [2][3][4][5][6][7][8][9][10][11]241. The pCMGTl-directed P1-4GalT in COS-1 cells was also activated by Mn2' and its optimal Mn2+ concentration was about 10 mM.…”
Section: Activation Q F U Fli-4gnlt H-v Mn2' Ionmentioning
confidence: 99%
“…It was reported that the lactose synthetase and other p1-4GalTs are activated by Mn2+, which is involved in maintaining the structural integrity of the enzyme, and the optimal Mn2+ concentrations of these enzymes were in the range of 10-15 mM [2][3][4][5][6][7][8][9][10][11]241. The pCMGTl-directed P1-4GalT in COS-1 cells was also activated by Mn2' and its optimal Mn2+ concentration was about 10 mM.…”
Section: Activation Q F U Fli-4gnlt H-v Mn2' Ionmentioning
confidence: 99%
“…The activity was detected in many mammalian cells and should also be present in nonmammalian tissues, according to published structures [4]. The enzyme has been partially purified from chick liver [5], pig trachea [6] and rat liver [7].…”
mentioning
confidence: 99%
“…1 a. The 1,4 activity is represented by closed circles; the 1,3 activity by open circles result from differences in the degrees ofsialylation. To test this possibility, both adult and embryonic galactosyltransferases from UDP-hexanohmine -Sepharose were treated with neuraminidase.…”
Section: Previous Work [ L ]mentioning
confidence: 99%